PENGEMBANGAN PARIWISATA PEDESAAN BERKELANJUTAN BERBASIS MODAL SOSIAL: MODEL YANG DAPAT DIREPLIKASI DARI WAWASAN DESA BUKIT LAWANG - Simanjuntak, Daniel; Supsilioani; Muhammad Iqbal; Zanrison Naibao; Dwikili (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2026)
The optimization of Social Capital in Indonesia’s sustainable rural tourism development is frequently constrained by inconsistent community participation. Previous research has demonstrated that a structured intervention, termed Social Engineering (SE), successfully optimizes Social Capital and triggers holistic village development. This study aims to test the universality and local contingency of that specific SE framework. Using the case study of Bukit Lawang village, we replicate the model's examination outside its original socio-cultural context in Sumatra (e.g., Java and Bali). The research posits that the success of this replication is fundamentally dependent on identifying socio-cultural contingency variables that necessitate adaptive implementation. The anticipated outcome is the formulation of an Adaptation Matrix for policy guidance, offering a tested implementation model to achieve inclusive, quantifiable (based on the Village Development Index/IPD), and sustainable growth across diverse cultural landscapes in Indonesia